The Hormonal Seed Priming in Relation to Carrot Germination - Filza Ghafoor; Sana Liaqat; Waseem Iqbal (Journal La Lifesci, 2020)
Seed priming is a pre-sowing treatment used to reduce stress effects in crops .This technique has been used to increase the germination rate of seeds mainly under unfavorable environmental condition. Crop productivity faces many problems like that unavailability of suitable condition that causes unbalanced seedling growth and poor germination. Hormones are essential to improve plant growth, development, crop yield quality and quantity. Auxin is essential hormones that improves germination of seeds and reduce stress effects. Laboratory experiment was conducted to study the effect of seed priming using different concentrations of IAA and IBA on carrot seeds (Daucus carota). In laboratory experiment, three concentrations of IAA and IBA (75 ppm, 50ppm, 25ppm) treated with distilled water with priming duration of 24 hours. Experiment was laid out in CRD with three replications. Data was collected to investigate the effect of seed priming with IAA and IBA under these condition like that (fresh weight, dry weight, speed of germination, root length, seed length, seedling length, final germination rate, mean germination time and dry matter content). Maximum fresh weight, final germination percentage, seedling length, energy of germination, speed of germination and mean germination rate was recorded IBA 75ppm. Maximum dry weight and dry matter content was observed IBA 25ppm.Maximum shoot length was recorded IBA 50ppm. Non-significant difference was recorded in root length.